Postural performance and strategy in the unipedal stance of soccer players at different levels of competition - Paillard, T.; Noe, F.; Riviere, T.; Marion, V.; Montoya, R.; Dupui, P. (Journal of Athletic Training, 2006)
Context: Sport training enhances the ability to use somatosensory and otolithic information, which improves postural capabilities. Postural changes are different according to the sport practiced, but few authors have analyzed subjects' postural performances to discriminate the expertise level among highly skilled athletes within a specific discipline.